De Re Diplomática. Las Fuentes ocasionales (Estudios humanísticos. Geografía, historia y arte, 2021)
Knowing the basic role of the document as a primary and fundamental source of the Diplomatics, the autor goes over the traditional scope and spreads the concept of source to other texts of narrative character, not strictly documentary, through the analysis of different examples of diverse nature and various times.